3D printing of meat. (July 2019) - Dick, Arianna; Bhandari, Bhesh; Prakash, Sangeeta
Abstract: Three-dimensional printing (3DP) process stands as a developing technology for food manufacturing, which offers the opportunity to design novel food products with improved nutritional value and sensorial profile. This review analyses the potential applications of 3DP technology for meat processing and the elemental aspects affecting the printability and post-processing feasibility of 3D printed meat products. The combination of nutritionally balanced ingredients and novel internal structures may be schemed into a multi-material 3D model that meets special individual needs, such as chewing and swallowing difficulties. Furthermore, a temperature-controlled extruder-type 3D printer built with multi-head system is suggested to suit the required conditions for meat safety and rheological requirements. Highlights: Multi-material 3D printing allows the production of recombined meats. The design of appetizing soft-meat products is viable with 3D printing technology. Low temperature-3D printers are needed to process meat products safely. The application of heat- and cold-set binders enhances the meat paste rheology.